Prolonged survival in patients with local chronic infection after high-grade glioma treatment: Two case reports - Solár, Peter; Mackerle, Zdenek; Hendrych, Michal; Pospisil, Petr; Lakomy, Radek; Valekova, Hana; Hermanova, Marketa; Jancalek, Radim (Frontiers in Oncology, 2022)
High-grade gliomas are primary brain tumors with poor prognosis, despite surgical treatment followed by radiotherapy and concomitant chemotherapy. We present two cases of long-term survival in patients treated for high-grade glioma and concomitant prolonged bacterial wound infection. The first patient treated for glioblastoma IDH-wildtype had been without disease progression for 61 months from the first resected recurrence. Despite incomplete chemotherapy-induced myelosuppression in the second patient with anaplastic astrocytoma IDH-mutant, she died without disease relapse after 14 years from the diagnosis due to other comorbidities. We assume that the documented prolonged survival could be related to the bacterial infection.